Herbert Hill and the Federal Bureau of Investigation - Phelps, Christopher (Taylor & Francis, 2012)
This article points to previously undetected evidence demonstrating that Herbert Hill, labor director of the National Association for the Advancement of Colored People (NAACP) from the 1950s to the 1970s, informed for the Federal Bureau of Investigation (FBI) on his former political associates in the Socialist Workers Party (SWP). It shows that the FBI subsequently sought to use Hill in 1962 to obstruct a rumored fraternization between the NAACP and the Committee to Aid the Monroe Defendants (CAMD), an organization initiated by SWP members in support of the black militant advocate of armed self-defense Robert F. Williams and the movement he led in Monroe, North Carolina. The article concludes by posing a series of questions raised by the evidence and connecting the matter to recent scholarship on the Cold War and civil rights activism.